Enhancing employability via ‘Thirdspace’ pedagogy and ethics - Badrul Redzuan Abu Hassan; Lee, Siew Chin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although the diversity of Malaysian pluralistic sociocultural society may present itself as a challenge in the maintenance of ethnic relations, it can perhaps be transformed, nevertheless, into a critical resource for graduate employability. Formal qualifications aside, Malaysian local graduates should be asking themselves whether they have the civic capacity and universal prerequisites as ‘glocalised’ employees of the future. In this paper, we will attempt to situate the discourse of employability within an ethical-pedagogical dimension of globalisation through social semiotics. It is suggested that insight into the ways of the globalised world may be provided through a pedagogic dimension known as ‘the Thirdspace’ (Bhabha, 1994), comprising a hybridized and cutting-edge space of ‘in-betweenness’ where diverse cultures meet and engage each other. This study takes off from a research on the perceived cultural and language competencies of undergraduates undertaken by a Malaysian university. Based on the findings of this research on the benchmarks for graduate competencies for future employability painted, a profile that went beyond the communicative and linguistic capabilities into elements such as attitudes, mindset and cultural awareness. With this in mind, this paper proposed that university curriculum utilises a Thirdspace pedagogy to expose and enhance cross-cultural literacies of Malaysian university undergraduates through socioculturally resonant Malaysian cinema.